Comparison of [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG Uptake in Esophageal Cancer - Liu, Huipan; Hu, Zhi; Yang, Xiao; Dai, Tianyang; Chen, Yue (Frontiers in Oncology, 2022)
Purpose Accurate clinical staging is crucial to managing esophageal cancer. [68Ga]Ga-DOTA-FAPI-04 exhibits good diagnostic performance in various tumors, showing a promising alternative to [18F]FDG. Here, we investigated the diagnostic performance of [68Ga]Ga-DOTA-FAPI-04 PET/CT and [18F]FDG PET/CT in the diagnosis of primary and metastatic lesions of esophageal cancer. Methods Patients with esophageal cancer who underwent concurrent [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG PET/CT between January 2020 and June 2021 were retrospectively analyzed. [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG PET/CT uptakes were compared by using the paired samples t test. The McNemar test was used to compare the diagnostic performance between the two techniques. Results Thirty-five patients (ranging from 44-83 years old with a median age of 63.5 years) were evaluated in our study. In treatment-naive patients (n=25), [68Ga]Ga-DOTA-FAPI-04 PET could detect all esophageal cancers, whereas 1 patient with superficial esophageal cancer was negative in FDG but positive in [68Ga]Ga-DOTA-FAPI-04 (T1). [68Ga]Ga-DOTA-FAPI-04 uptake was higher than [18F]FDG in primary lesions (13.8 ± 6.9 vs 10.9 ± 6.8, respectively, P=0.004), involved lymph nodes (9.3 ± 5.2 vs 6.4 ± 5.9, respectively, P=0.002), and bone and visceral metastases (10.4 ± 6.0 vs 6.1 ± 7.5, respectively, P=0.001). In addition, [68Ga]Ga-DOTA-FAPI-04 PET/CT has a higher detection sensitivity than [18F]FDG PET/CT for primary tumors [100% (25/25) vs. 96.0% (24/25), respectively], lymph nodes [95.0% (57/60) vs 75.0% (45/60), P<0.001], and bone and visceral metastases [100% (25/25) vs 72% (18/25), respectively; P= 0.008]. Conclusion [68Ga]Ga-DOTA-FAPI-04 PET/CT has higher tracer uptake value and is superior to [18F]FDG PET/CT in detecting primary and metastatic lesions in patients with esophageal cancer.